Cold‐crystallization behavior of poly(L‐lactide)/ACR blend films investigated by in situ FTIR spectroscopy. Issue 6 (7th June 2012) - Wu, Ningjing; Wang, Honghao; Ding, Meichun; Man, Liu; Zhang, Jianming
Abstract The cold crystallization behavior of poly (L‐lactide) (PLLA) blend films modified by small amount of acrylic rubber particles (ACR) have been investigated by in situ Fourier‐transform infrared (FTIR) spectroscopy. During the isothermal cold crystallization, the crystallization rate of PLLA is greatly improved with addition of only 1 wt % ACR. However, for PLLA with 8 wt % ACR, the crystallization rate is slower than that of neat PLLA. The relative crystallinity of PLLA with the addition of 1–5 wt % ACR is obviously higher than that of the neat PLLA. For the PLLA blend film with 3 % ACR, the relative crystallinity reaches a maximum. It was found that the addition of ACR particles below 5% accelerated the cold crystallization nucleation process and made the cold‐crystallization rate of PLLA/ACR be quicker than that of neat PLLA. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013